Genetic Meningococcal Antigen Typing System (gMATS): A genotyping tool that predicts 4CMenB strain coverage worldwide. Issue 7 (8th February 2019) - Muzzi, Alessandro; Brozzi, Alessandro; Serino, Laura; Bodini, Margherita; Abad, Raquel; Caugant, Dominique; Comanducci, Maurizio; Lemos, Ana Paula; Gorla, Maria Cecilia; Křížová, Pavla; Mikula, Claudia; Mulhall, Robert; et al.
Abstract: Background: The Meningococcal Antigen Typing System (MATS) was developed to identify meningococcus group B strains with a high likelihood of being covered by the 4CMenB vaccine, but is limited by the requirement for viable isolates from culture-confirmed cases. We examined if antigen genotyping could complement MATS in predicting strain coverage by the 4CMenB vaccine. Methods: From a panel of 3912 MATS-typed invasive meningococcal disease isolates collected in England and Wales in 2007–2008, 2014–2015 and 2015–2016, and in 16 other countries in 2000–2015, 3481 isolates were also characterized by antigen genotyping. Individual associations between antigen genotypes and MATS coverage for each 4CMenB component were used to define a genetic MATS (gMATS). gMATS estimates were compared with England and Wales human complement serum bactericidal assay (hSBA) data and vaccine effectiveness (VE) data from England. Results: Overall, 81% of the strain panel had genetically predictable MATS coverage, with 92% accuracy and highly concordant results across national panels (Lin's accuracy coefficient, 0.98; root-mean-square deviation, 6%). England and Wales strain coverage estimates were 72–73% by genotyping (66–73% by MATS), underestimating hSBA values after four vaccine doses (88%) and VE after two doses (83%). The gMATS predicted strain coverage in other countries was 58–88%. Conclusions: gMATS can replace MATS in predicting 4CMenB strain coverage in four out of five cases, without requiring a cultivable isolate, and is open to further improvement. Both methods underestimated VE in England. Strain coverage predictions in other countries matched or exceeded England and Wales estimates. An Audio Summary linked to this article that can be found on Figshare https://figshare.com/articles/gMATS_video_Vaccine-_2019-_37_7_991-1000_mp4/9326687